Urban Women's Resistance in Andina Dwifatma's Novel Entitled Lebih Senyap dari Bisikan: Karen Horney's Feminist Psychoanalysis Approach - Septina Munjariyati, Finda; Supriyanto, RM. Teguh; Setyaningsih, Nas Haryati (Universitas Negeri Semarang, 2022)
Urban women have complex problems compared to rural women, making urban women more vulnerable to experiencing various forms of gender injustice. The problems that occur to urban women are more often related to the economy caused by gender construction in society. The purpose of the research is to analyse the forms of resistance carried out by urban female characters in Andina Dwifatma's Novel Lebih Senyap dari Bisikan. The research method used is descriptive qualitative with Karen Horney's feminist psychoanalysis approach. The data collection technique used is heuristic reading technique. Data were taken in the form of quotations or sentences from Andina Dwifatma's Novel Lebih Senyap dari Bisikan. Data validity is done through intrarater test and transferability test. Data analysis technique using hermeneutic reading technique. The results of the research are the forms of resistance carried out by urban female characters against gender injustice, such as approaching others, fighting others, and staying away from others. The form of resistance carried out by Amara is by approaching others and staying away from others and fighting others. Meanwhile, Macan fights gender injustice by staying away from others.